2014
DOI: 10.4049/jimmunol.1400013
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-Catenin Pathway Attenuates Experimental Allergic Airway Disease

Abstract: Signaling via the Wnt/β-catenin pathway plays crucial roles in embryogenesis and homeostasis of adult tissues. In the lung, the canonical Wnt/β-catenin pathway has been implicated in remodeling processes, development of emphysema, and fibrosis. However, its relevance for the modulation of allergic responses in the lung remains unclear. Using genetically modified mice with lung-specific inducible (doxycycline) Wnt-1 expression (CCSP-rtTA × tetO-Wnt1), the impact of Wnt on the development of allergic airway dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 47 publications
3
33
0
1
Order By: Relevance
“…38 Furthermore, coculture of Wnt-treated DC with naïve T cells resulted in the induction of FoxP3-expressing regulatory T cells 38 and also exposure to Wnt1 markedly reduced the activation of effector T cells by DCs in coculture experiments. 39 Similar results were observed in a human cell coculture system. Exposure to Wnt5a resulted in increased secretion of IL-10 in blood-derived monocytes.…”
Section: Dendritic Cellssupporting
confidence: 75%
See 3 more Smart Citations
“…38 Furthermore, coculture of Wnt-treated DC with naïve T cells resulted in the induction of FoxP3-expressing regulatory T cells 38 and also exposure to Wnt1 markedly reduced the activation of effector T cells by DCs in coculture experiments. 39 Similar results were observed in a human cell coculture system. Exposure to Wnt5a resulted in increased secretion of IL-10 in blood-derived monocytes.…”
Section: Dendritic Cellssupporting
confidence: 75%
“…67 In addition, recent studies using LiCl in a murine model of allergic airway disease showed that treatment of sensitized animals before and during allergen challenge with LiCl reduced airway inflammation, hyperresponsiveness, and mucus production. 39 These finding add a mechanistic explanation to the observed effects in humans.…”
Section: Immunological Role Of Wnt Pathways In Asthmamentioning
confidence: 85%
See 2 more Smart Citations
“…Consistent with this, a recent study demonstrated that glycans associated with the mucin MUC2 in the gut imprinted DCs with tolerogenic properties via activation of β-catenin (144). Furthermore, a recent study has demonstrated a role for β-catenin in regulating DC function in the lung by blocking the migration of DCs from the lung to the draining LN and programming suppressive properties on such DCs (257).…”
Section: Control Of T Regulatory Responsesmentioning
confidence: 86%